2018
DOI: 10.5146/tjpath.2018.01422
|View full text |Cite
|
Sign up to set email alerts
|

Braf v600 mutation profile of metastatic melanoma in the thrace region of turkey

Abstract: Objective: BRAF is the most common mutation in melanoma. The most common subtype is BRAF V600E, followed by V600K. Initially, the authors aimed to investigate whether clinicopathological features of melanoma are associated with BRAF mutations. We then aimed to present the relationships between the clinicopathological features and the mutated subtype (V600E vs V600K). Material and Method:61 patients with metastatic malignant melanoma (affecting the lymph node or other distant sites) were selected. Patient data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…This result resembles the mutation prevalence found in Caucasian populations, which range around 40-60% [10]. Data on the nodular subtype from Asia is scarce with two studies reporting rates of 50 and 29.4% from Japan and Turkey, respectively [11,12]. The outcomes of our research are especially at odds with the result of our previous study using RT-PCR, which report a 10% BRAF V600 prevalence among Indonesian nodular melanomas [8].…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This result resembles the mutation prevalence found in Caucasian populations, which range around 40-60% [10]. Data on the nodular subtype from Asia is scarce with two studies reporting rates of 50 and 29.4% from Japan and Turkey, respectively [11,12]. The outcomes of our research are especially at odds with the result of our previous study using RT-PCR, which report a 10% BRAF V600 prevalence among Indonesian nodular melanomas [8].…”
Section: Discussioncontrasting
confidence: 46%
“…This mutation is found in 11.9 to 41.8% of Asian melanoma cases in general [5,12,16,17]. The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4 and 50% [11,12]. This suggests that Indonesian melanoma cases have a high BRAF V600 mutation prevalence, but at low intratumoral mutation rates.…”
Section: Discussionmentioning
confidence: 98%
“…There is little comparable data in Asia due to the limited studies on nodular melanomas. A study in Japan reported that 50% of nodular melanoma cases had the BRAF V600 mutation [6], while another research in Turkey stated the percentage at 29.4% [15].…”
Section: Discussionmentioning
confidence: 99%
“…This mutation is found in 11.9-41.8% of Asian melanoma cases in general (5,11,15,16). The only two studies on Asian nodular melanoma cases reported the mutation prevalence at 29.4% and 50% (10,11). This suggests that Indonesian melanoma cases have a high BRAF V600 mutation prevalence, as the subjects in this study were dominated by advanced extremity-located melanomas.…”
Section: Discussionmentioning
confidence: 94%